The use of nasal high flow oxygen to aid the management of respiratory failure and obesity in a district general maternity unit. Issue 2 (22nd October 2015) - McGovern, Christopher; Soosay, Alvin; Edwards, Jennifer; Williamson, Roy; Burns, Fergal; Chaudhri, Sofia
Summary: Nasal high flow (NHFTM) oxygen using the OptiflowTM system (Fisher & Paykel Healthcare Limited, Panmure, Auckland, New Zealand) is frequently used in our hospital in the management of type one respiratory failure. We present two cases where we have used NHFTM in our maternity unit. In the first case, this was used in the management of respiratory failure and as an adjunct at induction of general anaesthesia, and in the second, to facilitate safe neuraxial anaesthesia in a morbidly obese patient. Our experience of this equipment has prompted our department to consider its use beyond managing respiratory failure in critical care but also an adjunct for use in the operating theatres and maternity unit.